2023
DOI: 10.1007/s40618-023-02192-3
|View full text |Cite
|
Sign up to set email alerts
|

HPV-related diseases in male patients: an underestimated conundrum

A. Garolla,
A. Graziani,
G. Grande
et al.

Abstract: Purpose Human papillomavirus (HPV) infection is the most common sexually transmitted disease, in males and females worldwide. While the role of HPV in female diseases is well known and largely studied, males have negligibly been included in these programs, also because the proportion of women suffering and dying from HPV-related diseases is much larger than men. The aim of this review is to focus on HPV-related diseases in male patients. Methods We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 143 publications
0
6
0
Order By: Relevance
“…A few years later, Foresta et al [29] reported a strong correlation between asthenozoospermia, ASAs, and HPV sperm infection, regardless of the genotype, and further described in a subsequent study by Garolla et al [67]. Indeed, in several men with idiopathic asthenozoospermia, the presence of HPV DNA in semen appears to be the only risk factor detectable [29] (Table 1).…”
Section: Could Hpv-induced Anti-sperm Antibodies (Asas) Influence Mal...mentioning
confidence: 82%
“…A few years later, Foresta et al [29] reported a strong correlation between asthenozoospermia, ASAs, and HPV sperm infection, regardless of the genotype, and further described in a subsequent study by Garolla et al [67]. Indeed, in several men with idiopathic asthenozoospermia, the presence of HPV DNA in semen appears to be the only risk factor detectable [29] (Table 1).…”
Section: Could Hpv-induced Anti-sperm Antibodies (Asas) Influence Mal...mentioning
confidence: 82%
“…In addition, there is a concerning lack of awareness among adolescents, including medical students, regarding HPV and its vaccines. Greater efforts, potentially including mandatory measures, are required to increase awareness, particularly among males and young people ( 57 ). Accordingly, a risk-adaptive approach is necessary for patients with anal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although a possible correlation between HPV sperm infection, asthenozoospermia, and male fertility has been suggested ( 29 ), it is believed that HPV negatively affects the fertility of both males and females ( 30 ). Therefore, HPV infection of semen may be responsible for the reduction in natural and assisted pregnancy rates and a risk factor for pregnancy interruption ( 31 ). The exact mechanism by which sperm infection impairs fertility requires further investigation ( 22 , 30 ), considering that the transcriptional activity of HPV has never been detected in human semen ( 32 ).…”
Section: Discussionmentioning
confidence: 99%